Patient‐reported outcome measures within pediatric solid organ transplantation: A systematic review. (18th June 2019) - Anthony, Samantha J.; Stinson, Hayley; Lazor, Tanya; Young, Katarina; Hundert, Amos; Santana, Maria J.; Stinson, Jennifer; West, Lori
Abstract: Subjective evaluation of medical care and disease outcomes from patients' perspectives has become increasingly important. Patient‐reported outcome measures (PROMs) play a prominent role in engaging patients, capturing their experiences and improving patient care. This systematic review sought to identify PROMs that are used in the field of pediatric solid organ transplantation, with the aim to inform the implementation of PROMs into clinical practice for this population. A systematic review of English language, peer‐reviewed articles was performed on key health science databases to identify publications using PROMs in pediatric solid organ transplantation. The search yielded 3670 articles, with a final data set of 62 articles that included 47 different PROMs. The three most frequently used PROMs included the following: (a) PedsQL™ Generic Core Scales (n = 25); (b) Children's Depression Inventory (n = 6); and (c) Child Health Questionnaire (n = 6). Of the 47 PROMs, 42 were generic and five were disease‐specific; only six PROMS had a documented psychometric evaluation within a pediatric solid organ transplant population. This review outlines the attributes of the instruments (eg, domains captured), as well as the psychometric properties of those evaluated. PROMs are increasingly used in the field of pediatric transplantation; however, there are limited details in the current literature about their conceptual underpinnings and psychometric properties. This review highlights the need for additional psychometric evaluation of identified measures to establish the necessary foundation to inform the implementation of PROMs into clinical care for pediatric solid organ transplant patients.